Comparative Analysis of the Influence of FDI Inflows on Economic Development Between Serbia and Poland - Hasan Hanic; Tijana Kalicanin; Dusko Bodroza (Institute of Economic Research (IER), 2017)
The aim of this paper is to measure the impact of the FDI on the economic growth in Poland and on the economic growth in Serbia and further to make comparative analysis of the impact between these two countries. Empirical studies showed that FDIs can make crowding-out effect, i.e. FDIs can out crowd domestic investments which further have more impact on the economic growth. Because this effect depends on the specific level of the development of the country, the aim is to compare the influence of the FDI on economic growths on both of them as long as Poland is classified as a developed country and Serbia is a country which belongs to the group - countries in transition. Panel data includes variable values from 1999-2007, until global economic crisis period and 2008-2015, period after crisis in order to see flows and make comparison between these two periods. GDP is the main indicator which represents economic growth. According to that, using regression analysis, the aim is to measure influence of FDIs as the independent variable on real GDP growth, as dependent variables. Besides, a group of control variables are included in the method. As long as GDP is enhanced by lower inflation, inflation will be used as independent variable. Our model also includes determinants of monetary and government sectors such as official exchange rate, inflation and government consumption. Using two multiple linear regression models we found the significant influence of FDI inflows on economic growth in Poland. Using the same models for observations in Serbia we haven't found significant effects of FDI Inflows on economic growth.
Keywords: A11; 330; FDI; economic growth; development; investments